Remplissage et solidification par elements finis - Dhatt, G.; Gao, D.N.; Medal, M.; Song, R. (European Journal of Computational Mechanics, 1992)
The solidification and filling of castings in foundary are simulated by a finite element model. The moving fronts are captured by F- function technique using a fu:ed mesh. An enthalpie model with mushy nodal zones is employed for solidification. We follow the solution along H - T curve by a constant enthalpie return technique. Different examples are presented to demonstrate the model capabilities.